A “Whole of system approach” to develop environmental sustainability in a Singapore Healthcare System - Brandon X. Lum; Rebecca Y. Lee; Boon Woei Lee; Bee Lok Hoong; Eugene H. Liu (The Journal of Climate Change and Health, 2025)
Introduction: While healthcare systems have to prepare for the impact on global health due to climate change, the healthcare sector must reduce carbon emissions and become environmentally sustainable. This paper provides an overview of how a healthcare system in Singapore, the National University Health System (NUHS), is transiting to sustainable healthcare. Case presentation: NUHS used a “whole of system approach”, developing a system for governance, accountability, and management, and building internal capability to decarbonize healthcare. This was managed by a newly formed Office of Sustainability, to address the system's carbon footprint in clinical care, facilities management, and procurement. Strategies on sustainability focused on emissions and consumption that were material and significant to NUHS were pursued. Discussion: NUHS encountered several challenges in the implementation of certain initiatives such as limited manpower and funding, managing supplier relationships and changing clinical practices. A key focus was to build internal capabilities and prioritize strategies to drive sustainability within the health system. Ensuring the availability of funding enabled the implementation of sustainability initiatives as well. Additionally, a growing workload with Singapore's aging local population would reduce the impact of sustainability initiatives on NUHS’ carbon footprint. Conclusion: This paper aims to assist other healthcare systems embarking on their sustainability journeys to formulate a plan to decarbonize.